Fear of small numbers an essay on the geography of anger - Appadurai, Arjun 1949- (Public planet books, 2006)
From ethnocide to ideocide -- The civilization of clashes -- Globalization and violence -- Fear of small numbers -- Our terrorists, ourselves -- Grassroots globalization in the era of ideocide